PENGUJIAN DISTRIBUSI BEBAN KERJA WEB PADA SISTEM SERVER WEB BERBASIS CLUSTER DENGAN ALGORITMA LEAST CONNECTION DAN WEIGHTED LEAST CONNECTION - , Nongki Angsar ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The growth of web traffic and network bandwidth which is quicker than the growth of microprocessor these days cause single server platform no longger be adequate to fulfill the requirement of web server system scalability. Plural server platform is the answer. One of solutions which have been recognized is cluster-based web server system. This research did some web workload distribution tests on a cluster-based web server system by generating HTTP workload staticly (with constant HTTP request rate) and dynamicly (with continuous changing HTTP request rate) from client to web server system pool. Continued with data packet traffic analysis. And then, compare web workload distribution test results (HTTP reply rate, response time, and throughput) between Least Connection / LC algorithm (weightless) and Weighted Least Connection / WLC algorithm (with weight). Result of tests indicate that WLC algorithm is better than LC algorithm in distributing HTTP request and HTTP reply, but WLCâs response time is slower than LC. While throughput of WLC and LC is equal in size.